2016
DOI: 10.1371/journal.pcbi.1005019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Reweighting of Auditory Modulation Filters

Abstract: Sound waveforms convey information largely via amplitude modulations (AM). A large body of experimental evidence has provided support for a modulation (bandpass) filterbank. Details of this model have varied over time partly reflecting different experimental conditions and diverse datasets from distinct task strategies, contributing uncertainty to the bandwidth measurements and leaving important issues unresolved. We adopt here a solely data-driven measurement approach in which we first demonstrate how differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…This could be a first reason explaining why we did not observe any learning between the beginning and the end of the experiment. Note that previous studies using masking modulation paradigms found plasticity for AM-processing (Joosten et al, 2016) but not with STM-processing (Oetjen & Verhey, 2015). Second, it is possible that the learning occurred extremely rapidly during the initial training phase or pre-test (see Grant et al 2013) and could therefore not be exposed here, since our pre- and post-tests were scheduled at the end of the training session and the final session, respectively.…”
Section: Supplementary Materialsmentioning
confidence: 81%
See 4 more Smart Citations
“…This could be a first reason explaining why we did not observe any learning between the beginning and the end of the experiment. Note that previous studies using masking modulation paradigms found plasticity for AM-processing (Joosten et al, 2016) but not with STM-processing (Oetjen & Verhey, 2015). Second, it is possible that the learning occurred extremely rapidly during the initial training phase or pre-test (see Grant et al 2013) and could therefore not be exposed here, since our pre- and post-tests were scheduled at the end of the training session and the final session, respectively.…”
Section: Supplementary Materialsmentioning
confidence: 81%
“…These filters show different patterns for target-absent vs. target-present stimuli in both groups, exposing the presence of non-linear processes unaccounted for by a template-matching strategy (Neri, 2004; Tjan & Nandy, 2006; Neri, 2010b). These departures from template-matching are accommodated by a small cascade model consisting of a front-end STM weighting function followed by a MAX operation (see also Joosten et al, 2016). Because this cascade structure is applicable to both NH and HI groups, this result indicates that hearing-impaired listeners rely on intact circuitry for monitoring the output of their modulation channels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations